Barriers and facilitators to return to work following cardiovascular disease: a systematic review and meta-synthesis of qualitative research - Maria Kristiansen; Emma Borre Andersen; Sidsel Marie Bernt Jørgensen (BMJ Open, 2023)
Objectives Return to work is a key rehabilitation goal, however, people recovering from cardiovascular disease (CVD) often struggle with returning to work. The aim of this study was to conduct a systematic review and meta-synthesis of the existing qualitative evidence on barriers and facilitators to return to work experienced by people with CVD.Methods A systematic literature search was conducted in PubMed, Embase, Web of Science, PsycINFO, Scopus and CINAHL in August 2022. The reference lists of the included articles were searched. The Critical Appraisal Skills Programme was used for quality appraisal and a meta-synthesis was employed.Findings This review includes 15 studies of overall high methodological quality. Barriers covered four themes: physical limitations, psychological and relational factors, the working context and support within health and social care systems. Facilitators were related to five themes: return to normality, enhancing well-being, financial concerns, the working context and support within health and social care systems.Conclusion Our findings highlight that return to work following CVD is a complex process influenced by individual factors, as well as work-related factors, factors in the health and social care systems and social security policies and regulations. To improve return to work, this review illustrates a need for individualised, multidisciplinary and coordinated vocational rehabilitation programmes that accommodate potential barriers to re-employment. Similarly, this review highlights how vocational rehabilitation programmes should ensure individualised information and support early in the rehabilitation process, as well as the importance of engaging relevant stakeholders, such as employers, in making individualised return-to-work plans.